Genetic dissection of the grain-filling rate and related traits through linkage analysis and genome-wide association study in bread wheat - Hai-xia YU; Xi-xian DUAN; Ai-qing SUN; Xiao-xiao SUN; Jing-juan ZHANG; Hua-qing SUN; Yan-yan SUN; Tang-yuan NING; Ji-chun TIAN; Dong-xue WANG; Hao LI; Ke-xin FAN; et al. (Journal of Integrative Agriculture, 2022)
Wheat grain yield is generally sink-limited during grain filling. The grain-filling rate (GFR) plays a vital role but is poorly studied due to the difficulty of phenotype surveys. This study explored the grain-filling traits in a recombinant inbred population and wheat collection using two highly saturated genetic maps for linkage analysis and genome-wide association study (GWAS). Seventeen stable additive quantitative trait loci (QTLs) were identified on chromosomes 1B, 4B, and 5A. The linkage interval between IWB19555 and IWB56078 showed pleiotropic effects on GFR1, GFRmax, kernel length (KL), kernel width (KW), kernel thickness (KT), and thousand kernel weight (TKW), with the phenotypic variation explained (PVE) ranging from 13.38% (KW) to 33.69% (TKW). 198 significant marker-trait associations (MTAs) were distributed across most chromosomes except for 3D and 4D. The major associated sites for GFR included IWB44469 (11.27%), IWB8156 (12.56%) and IWB24812 (14.46%). Linkage analysis suggested that IWB35850, identified through GWAS, was located in approximately the same region as QGFRmax2B.3-11, where two high-confidence candidate genes were present. Two important grain weight (GW)-related QTLs colocalized with grain-filling QTLs. The findings contribute to understanding the genetic architecture of the GFR and provide a basic approach to predict candidate genes for grain yield trait QTLs.